Within-herd spread of contagious bovine pleuropneumonia in Ethiopian highlands - Lesnoff, Matthieu; Laval, G.; Bonnet, P.; Abdicho, S.; Workalemahu, A.; Kifle, D.; Peyraud, A.; Lancelot, R.; Thiaucourt, Francois (Elsevier, 2004)
Contagious bovine pleuropneumonia (CBPP) is a major threat for cattle health and production in Africa. This disease is caused by the small-colony type of Mycoplasma mycoides subspecies mycoides (MmmSC). Transmission occurs from direct and repeated contacts between sick and healthy animals. Veterinary services recently reported a resurgence of CBPP in the province of West Wellega, in the Ethiopian highlands. A research program was set up to estimate the epidemiological parameters of the within-herd infection spread. A follow-up survey was implemented in 71 sampled herds of the Boji district (West Wellega province). Fifteen herds were classified as newly infected and used in a serological- and clinical-incidence study. The overall 16-month cumulative sero-incidence risk was 34%. Clinical cases were recorded for 39% of the seropositive cattle; case-fatality risk was 13%. There was no evidence of benefit on infection spread of CBPP-control measures used locally by farmers (isolation or antibiotic treatments of sick animals). This might be related to a lack of power in the statistical analyses or to a quality problem for the medications used (and more generally, for health-care delivery in the Boji district).